Molecular Mechanisms of Pulmonary Fibrosis and Current Treatment - Kuwano, K.; Hagimoto, N.; Hara, N. (Current Molecular Medicine, 2001)
Pulmonary fibrosis is a common response to various insults or injuries to the lung. Although there are various initiating factors or causes, the terminal stages are characterized by proliferation and progressive accumulation of connective tissue replacing normal functional parenchyma. The pathogenesis of pulmonary fibrosis includes endothelial and epithelial cell injury, production of inflammatory cells and their mediators, and fibroblast activation. Conventional therapy consisting of glucocorticoids or cytotoxic drugs is usually ineffective in preventing progression of the disease. Further understanding of the molecular mechanisms of endothelial and epithelial cell injury, inflammatory reaction, fibroblast proliferation, collagen deposition and lung repair, should lead to the development of effective treatments against pulmonary fibrosis. Accordingly, this review summarizes recent progress made in understanding the molecular mechanisms of pulmonary fibrosis. A detailed discussion is presented regarding each of the potential new therapies which have emerged from the animal models of pulmonary fibrosis and which have been developed through advances in cellular and molecular biology.
Keywords: Idiopathic Pulmonary Fibrosis